Constitution in the Age of Algorithms: Reinterpreting the Rule of Law in the Context of Digital Constitutionalism in Indonesia - Marzuki Lubis; Muhammad Ridwan Lubis (International Forum of Researchers and Lecturers, 2026)
The rapid expansion of algorithm-driven digital platforms has transformed the relationship between the state, citizens, and private technology companies, creating constitutional challenges beyond conventional constitutional law. Algorithmic governance increasingly enables private platforms to influence freedom of expression, privacy, access to information, and other constitutional rights, prompting the emergence of Digital Constitutionalism. However, existing scholarship largely emphasizes European and North American perspectives, while Indonesia remains underexplored. This study examines how the rule of law should be reinterpreted to address the constitutional implications of algorithmic governance in Indonesia. Using normative legal research with constitutional, statutory, conceptual, and comparative approaches, it analyzes constitutional provisions, legislation, judicial decisions, international legal instruments, and academic literature. The findings show that Indonesia's constitutional framework still focuses on state–citizen relations, despite the growing constitutional influence of digital platforms. Therefore, rule of law principles—including legality, legal certainty, due process, transparency, accountability, and equality before the law—should be reconstructed to accommodate algorithmic governance. The study proposes an Indonesian Digital Constitutionalism Framework that strengthens constitutional protection of digital human rights while providing guidance for constitutional reform, digital governance regulation, and democratic accountability in the digital era.